LMS ADOPTION IN A CORPORATE UNIVERSITY: INSIGHTS FROM SUS EVALUATION AND AN UTAUT-INFORMED QUALITATIVE ANALYSIS - Sartika, Venny; Permana, Muhammad Yorga (Journal of Economic, Bussines and Accounting (COSTING), 2025)
This study aims to quantitatively examine the structural relationships among destination image quality of tourist experience tourist trust and revisit intention at Widuri Beach Pemalang using a statistical approach based on SPSS. The research employed a quantitative design with data collected through a questionnaire survey administered to 150 tourists who had visited Widuri Beach Pemalang. The sampling technique used was accidental sampling. Data analysis included validity reliability correlation and multiple regression tests. The findings indicate that destination image quality of tourist experience and tourist trust have significant effects both partially and simultaneously on tourists revisit intention to Widuri Beach Pemalang. Practically this study highlights the importance of strengthening destination image building tourist trust and enhancing the quality of tourist experiences to support the sustainability and competitiveness of Widuri Beach at national and international levels.